EFFECT OF ADDITION OF THE CUO-FE2O3 SYSTEM ON THE ELECTROMAGNETIC-WAVE ABSORBING PROPERTIES OF SINTERED FERRITE - KIM, KY; KIM, WS; JU, YD; JUNG, HJ (CHAPMAN HALL LTD, 1992)
The effects of the addition of the CuO-Fe2O3 system as a liquid former on the microstructure and electromagnetic wave absorbing property of sintered Ni-Zn ferrite were investigated. The CuO-Fe2O3 system, a spinel ferrite, has its own magnetic property, which enables it to be used as an electromagnetic wave absorber. The CuO-Fe2O3 system was preferentially located at the grain boundary in the matrix of an Ni-Zn ferrite. This resulted in an increase in the total loss and a decrease in matching thickness. The centre frequency shift is presumed to occur because Ni-Zn ferrite with CuO-Fe2O3 behaves like a mixture of two ferrites with loss characteristics at the different frequency ranges.